SAINS DALAM BINGKAI ISLAM: Pemikiran Konseptual, Prinsip Dasar, dan Arah Implementasi Islamisasi Ilmu - Alsyah Nayla Fajrin Fajrin (J-PAI NIDA EL-ADABI: Jurnal Pendidikan Agama Islam, 2026)
The debate regarding the relationship between modern science and Islam continues to evolve in the field of contemporary Islamic education. Various studies have addressed the concept of the Islamization of science, but most have focused on philosophical aspects or the thought of specific figures; consequently, few have integrated discussions on the conceptual foundations of science in Islam, the epistemological principles of the Islamization of science, and the direction of its implementation in contemporary education and research. This study aims to analyze conceptual thinkingabout science in Islam, explain the basic principles of the Islamization of science according to Ismail Raji al-Faruqi, and identify the direction of its implementation in the context of higher education and research. This study employs a qualitative approach using a literature review method through thematic analysis of various relevant primary and secondary sources. The results indicate that scientific thought in Islam is grounded in the principle of tawhid, which views religion and science as a complementary unity in understanding reality. This study also found that al-Faruqi’s concept of the Islamization of science is built upon five principles of unity: God, creation, truth and knowledge, life, and humanity. Unlike previous studies that tend to remain at the conceptual level, this research offers a more operational implementation framework through the integration of an Islam-based worldview curriculum, the development of research methodologies that consider empirical and ethical dimensions, and the strengthening of interdisciplinary collaboration between scientists and Islamic scholars. This study positions the Islamization of science as one approach within the evolving discourse on the integration of science and religion; thus, its relevance must be critically and dialogically understood in relation to various other paradigms in contemporary Islamic education